Analysis of operations in the energy market in a deregulated environment. Issue 12 (1st December 2016) - Gupta, Divya; Jain, Sanjay Kumar
ABSTRACT: The energy markets should be deregulated to get a reliable power system. The important factors indicating this scenario is to find out the best value of available transfer capability, system cost, and loading of lines. Sometimes, these factors become contradictory to each other so much that if one decreases, the other increases. In this paper, a 10-bus system is taken and the values of these factors are calculated by considering various transactions in the power system simulation environment. This system is divided into two Areas A and B. Also, the economic cost of each combination is determined to visualize the impact of the change in transactions between areas on the cost. The results of these transactions are then compared based on several factors to get the economic cost energy operation.